Hubungan Efikasi Diri dengan Perilaku Manajemen Hipertensi - Rasdiyanah - Rasdiyanah; Eka Rahmatia; Syisnawati Syisnawati (Jurnal Gema Keperawatan, 2022)
Non-communicable disease is the main cause of death worldwide, one of the non-communicable diseases is hypertension, hypertension is a major factor in heart disease and stroke which can cause disability worldwide. The increase in the prevalence of hypertension is caused by poor hypertension management so that it has an impact on the quality of individual health. The aim of the study is to determine the relationship between self-efficacy and hypertension management behavior in the community of Pacellekang Village. Research design is correlational analytical descriptive using a cross sectional study approach. the sampling technique uses non-probability sampling with purposive sampling technique. The samples obtained in this research are 60 people. Data collection Uses the HBP-SCP Questionnaire in July 2022. Based on the results of the study, it was shown that respondents had high self-efficacy with an average score of 54.00 and good behavior, namely 55.00. Based on the results of the linear regression test using the spearman rank test, it was found that there was a significant relationship between self-efficacy and hypertension management behavior in the community of Pacellekang Village P value 0.001 0.05. The conclusion of this study is that the self-efficacy description of the respondents is stated to be high generally and the behavior of hypertension management in Pacellekang Village is stated to be good. There is a significant relationship between self-efficacy and hypertension management behavior in the community of Pacellekang Village.